2021
DOI: 10.3389/fevo.2021.704105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simulated Heat Wave on Oxidative Physiology and Immunity in Asian Yellow Pond Turtle (Mauremys mutica)

Abstract: Global warming has led to an increase in the frequency, duration, and intensity of heat waves in the summer, which can cause frequent and acute heat stress on ectotherms. Thus, determining how ectothermic animals respond to heat waves has been attracting growing interest among ecologists. However, the physiological and biochemical responses to heat waves in reptiles, especially aquatic reptiles, are still poorly understood. The current study investigated the oxidant physiology, immunity, and expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Similar results were found in P. guttatus in the acclimation to simulated heat wave, in which the antioxidative capacity did not change but the oxidative damage level obviously decreased (Stahlschmidt et al, 2017). On the contrary, although the activity of T-SOD and CAT, and T-AOC are not affected by heat wave, the GPX activity in the muscle in M. mutica significantly increased (Li et al, 2021). The activities of antioxidant enzymes were attenuated for N. pleskei in the acclimation to simulated heat wave, but its oxidative damage level dramatically decreased.…”
Section: Antioxidant Defense Systemsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results were found in P. guttatus in the acclimation to simulated heat wave, in which the antioxidative capacity did not change but the oxidative damage level obviously decreased (Stahlschmidt et al, 2017). On the contrary, although the activity of T-SOD and CAT, and T-AOC are not affected by heat wave, the GPX activity in the muscle in M. mutica significantly increased (Li et al, 2021). The activities of antioxidant enzymes were attenuated for N. pleskei in the acclimation to simulated heat wave, but its oxidative damage level dramatically decreased.…”
Section: Antioxidant Defense Systemsupporting
confidence: 80%
“…However, the telomere length and overwinter survival of desert toad-headed agama (Phrynocephalus przewalskii) were shortened after exposure to a stimulated heat wave (Zhang et al, 2018). In Asian yellow pond turtle (Mauremys mutica), heat wave does not significantly affect the level of MDA in the liver and muscle (Li et al, 2021). Therefore, heat wave has different physiological effects on different species, positive or negative.…”
Section: Oxidative Stress and Oxidative Damagementioning
confidence: 99%
“…The antioxidant defense may be the most important physiological adjustment when animals are exposed to heat waves (Troschinski et al, 2014;Baker et al, 2020). Extremely high temperatures would seriously increase the metabolic rates and synchronously produce reactive oxygen species (ROS;Ben Ameur et al, 2012), which would react with the molecular components of cells, such as lipids, proteins, and nucleic acids, leading to oxidative damage in cell machinery, indicated by the content of malondialdehyde (MDA), carbonylated protein, and DNA injury (Li et al, 2021). The accumulation of oxidative damage then induces the collapse of functions such as immunity, and even leads to mortality of the individuals; hence, depressed immunity can serve as a proxy for oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, heat waves induce oxidative damage (e.g., MDA) and affect immunity; however, individuals can enhance their antioxidant defense to reduce the potential threat of heat waves (Speakman and Garratt, 2014). For example, our previous study demonstrated that when yellow pond turtles (Mauremys mutica) faced heat waves, enhanced GPx facilitated antioxidant defense and plausibly reduced the production of MDA (i.e., oxidative damage), thereby sustaining innate immunity, including increased lysozyme activity and serum complement C4 levels (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation